Magnetoelastic properties of terbium substituted cobalt ferrite - Bhame, Shekhar D.; Joy, Pattayil Alias (Chemical Physics Letters, 2017)
The magnetic properties of terbium substituted cobalt ferrites CoFe(2-x)TbxO(4) (x = 0, 0.05, 0.1, 0.15 and 0.2) prepared by conventional solid state method are studied. The coercivity showed marked increase up to x = 0.1 and saturation magnetization decreased with increasing terbium content. Magnetostriction measurements did not show much decrease in the maximum value of strain but significant increase in the slope of magnetostriction was observed for x = 0.15 with moderate magnetostriction of around 144 ppm. The observed magnetic and magnetostrictive properties can be explained on the basis of structural and microstructural changes arising because of terbium substitution. (C) 2017 Elsevier B.V. All rights reserved.